2017
DOI: 10.1128/jvi.00410-17
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity and Epitope Exposure of the HIV-1 Envelope Trimer

Abstract: We recently showed that mutations in the HIV-1 envelope (Env) destabilize the V3 loop, rendering neutralization-resistant viruses sensitive to V3-directed monoclonal antibodies (MAbs). Here, we investigated the propagation of this effect on other Env epitopes, with special emphasis on V2 loop exposure. Wild-type JR-FL and 19 mutant JR-FL pseudoviruses were tested for neutralization sensitivity to 21 MAbs specific for epitopes in V2, the CD4 binding site (CD4bs), and the CD4-induced (CD4i) region. Certain glyca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 73 publications
6
37
0
Order By: Relevance
“…5I and Table 3). Mutation L125F was previously reported to be an important determinant of intraprotomer interactions between V1/V2 and V3 in strain JR FL , allowing the exposure of both V2 and V3 neutralizing epitopes (42). Those studies also identified residue I184 as a potential interprotomer V1/V2 interaction partner with residue 165, consistent with our work identifying I165 as a key determinant of trimer opening in JR CSF Env.…”
Section: Discussionsupporting
confidence: 91%
“…5I and Table 3). Mutation L125F was previously reported to be an important determinant of intraprotomer interactions between V1/V2 and V3 in strain JR FL , allowing the exposure of both V2 and V3 neutralizing epitopes (42). Those studies also identified residue I184 as a potential interprotomer V1/V2 interaction partner with residue 165, consistent with our work identifying I165 as a key determinant of trimer opening in JR CSF Env.…”
Section: Discussionsupporting
confidence: 91%
“…In previous reports, I184 of one protomer has been shown to interact with L165 of the neighbouring protomer. This inter-protomeric interaction has been shown to be critical for quaternary interactions leading to the stabilization of the V1V2 regions of neighbouring protomers, and its loss has been shown to render JR-FL, a clade B HIV-1 strain, highly sensitive to V3 mAbs (42, 43). On similar lines, we observed L184 of one promoter interacting with R165 of another protomer [via van der Waals interactions between the solvent-accessible surface (SAS) of R165 and L184 on neighbouring protomers] ( Figure 8A ).The side chain of L184 was observed to be outward facing and did not make significant intra-protomeric interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Substitution of the small side chain of leucine with the bulky non-polar side chain of phenylalanine led to disruption of interprotomer interactions that have been observed to be critical for maintenance of the trimeric apex. Mutations that alter or disrupt interprotomer contacts in Env trimer have been shown to change its susceptibility to several classes of bnAbs (39, 4143). Overall, our results provide information on the role of a rare escape mutation L184F in the viral envelope that led to resistance to bnAbs targeting the V2-apex.…”
Section: Discussionmentioning
confidence: 99%
“…Beginning from a closed state in which the trimer apex and topological layers surround the gp41 three-helix bundle 49 , engagement of a single CD4 induces β20-β21 loop rearrangement and is associated with Env triggering via residue I432 in β20-β21 and residue L193 in V1/V2. 30 Instability in V1/V2 associated with these changes would allow V3 exposure 34,50 and initial apex dissociation of a single gp120 protomer from the gp41 three-helix bundle 31 . Internal configurational changes in V1/V2 could then propagate to layers-1 and 2, thereby releasing W571, thus lowering the potential energy barrier to full gp120-gp41 three-helix bundle dissociation resulting in a single gp120 open, asymmetric trimer configuration.…”
Section: Discussionmentioning
confidence: 99%